Assessing the Influence of Socio-Demographic Factors on Road Traffic Injuries and Fatalities in Nepal (The Journal of Nuwakot Adarsha Multiple Campus, 2024)
The impact of socio-demographic factors on road traffic injury and death rates in Nepal was studied using data from the 2022 National Demographic and Health Survey (NDHS). A two-stage stratified cluster sampling method was utilized to gather information from 14,280 households in urban and rural areas. Descriptive statistics were employed, and multiple regressions were conducted to explore road traffic injuries as the dependent variable and age, gender, education, income, and place of residence as the independent variables. The findings reveal that accident rates are highest among young adults aged 15-34 years, while mortality is most prevalent in individuals aged 60 years and above. The distribution of injuries and fatalities varied across regions, with Karnali and Sudurpashchim provinces reporting the highest combined numbers. Additionally, social status played a role in the likelihood of accidents, with the most economically disadvantaged individuals being more vulnerable to severe crashes due to limited and less secure transportation options. The majority of motorcycle traffic casualties involved men, while women were more frequently affected by bus and bicycle accidents. This research highlights the impact of socio-demographic factors on the frequency of road traffic injuries and fatalities in Nepal and suggests the need for further investigation into addressing infrastructure, alcohol and drug use, and distractions to prevent road traffic accidents in the country.